Extreme Electron‐Photon Interaction in Disordered Perovskites - Sergey S. Kharintsev; Elina I. Battalova; Ivan A. Matchenya; Albert G. Nasibulin; Alexander A. Marunchenko; Anatoly P. Pushkarev (Advanced Science)
Abstract The interaction of light with solids can be dramatically enhanced owing to electron‐photon momentum matching. This mechanism manifests when light scattering from nanometer‐sized clusters including a specific case of self‐assembled nanostructures that form a long‐range translational order but local disorder (crystal‐liquid duality). In this paper, a new strategy based on both cases for the light‐matter‐interaction enhancement in a direct bandgap semiconductor – lead halide perovskite CsPbBr3 – by using electric pulse‐driven structural disorder, is addressed. The disordered state allows the generation of confined photons, and the formation of an electronic continuum of static/dynamic defect states across the forbidden gap (Urbach bridge). Both mechanisms underlie photon‐momentum‐enabled electronic Raman scattering (ERS) and single‐photon anti‐Stokes photoluminescence (PL) under sub‐band pump. PL/ERS blinking is discussed to be associated with thermal fluctuations of cross‐linked [PbBr6]4‐ octahedra. Time‐delayed synchronization of PL/ERS blinking causes enhanced spontaneous emission at room temperature. These findings indicate the role of photon momentum in enhanced light‐matter interactions in disordered and nanostructured solids.